Construction and Standardization of Cleanliness Attitude Scale (CAS) - sharma, gouri (IJRDO- Journal of Educational Research, 2021)
The paper deals with the development and standardization of cleanliness attitude scale (CAS) for women residing in slum areas. At the initial stage, the scale consisted of 100 items, then the items were reduced to 54 after extensive scrutiny by the subject experts. Subsequently item analysis was carried out. Finally, a set of 38 items was retained for the final scale. The final version of the cleanliness attitude scale consists of 20 positive and 18 negative items. The reliability of the scale was ascertained by Cronbach Alpha and it was found significant. Content validity and face validity was also determined by evaluation from subject experts. For the interpretation of data norms was also established.